Financial modeling for decision making : using MS-Excel in accounting and finance - Messer, Ron (Emerald Publishing Limited, 2020)
This book provides accounting students in post-secondary institutions with an advanced level understanding of how to use MS-Excel to make business decisions. It reflects real-life applications of this important analytical tool, which has become the accepted industry standard for spreadsheet software.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Account books; Electronic spreadsheets; Business enterprises -- Finance; Business & Economics -- Accounting -- General; Financial accounting